Pengaruh Modal, Jumlah Anggota dan Aset Tetap terhadap Sisa Hasil Usaha pada Koperasi Syariah Rinjani Perkasa - Oktaviani, Susi; Septiawati, Rohma; Nasihin, Ihsan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Cooperatives as different entities are expected to be able to plan and provide financial reports by understanding the appropriate PSAK. In this examination PSAK Syariah No. 102. The dangerous characteristic that is the focal point of this examination is the striking uncertainty in the Remaining Work Results (SHU) of Rinjani Perkasa's Sharia Assistant during the 2018-2022 period. This exploration was led at Rinjani Perkasa Sharia Agreeable. This kind of quantitative expressive exploration. The type of information for this examination is optional information. Information checking techniques use the Enlightenment Test, Exemplary Suspicion Test consisting of Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Assurance Test, Investigation of Various Direct Relapses and Speculation Test with the SPSS 26 investigation tool. The consequences of this research clearly affect the capital variable on the rest. organizational results. The variable number of individuals has a negative impact on excess business results. Resource factors continue to impact the remaining business results. Apart from that, capital factors, number of individuals and fixed resources also have an impact on excess business results.